Role of Natural Epizootics of a Npv Disease in Controlling Prosopis juliflora Defoliator Taragama siva Outbreak in North- West Rajasthan - Ahmed, S. I.; Kumar, Shivesh (Indian Forester, 1998)
The field population of Taragama siva Lefebvre, a polyphagous forest insect pest, was noticed severely infected with a polyhedrosis virus, at Jodhpur and adjacent localities during AugustSeptember, 1995. In field studies, a high incidence of disease was present in young larval population. Sample oflate instar larvae collected from field showed 96.66 per cent infected material. Although, one species ofa dipterous parasite is known to attack T. siva, but control by this agent, in the present study, appeared negligible. The number of cocoons formed at the end of outbreak was extremely low. There was good evidence to suggest that the virus infection was the main cause in the sudden collapse of pest population.